Local Protests Against Over Tourism: Causes, Effects and Solutions - Çiçekdağı, Münevver (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explores the causes of anti-tourism protests and highlights measures to prevent their negative impact on regional tourism sustainability. Local behaviours are analysed through Doxey's Tolerance Model and Social Exchange Theory. Over tourism and the protests organized by local people due to this situation constitute important problems in terms of sustainable tourism. In the study conducted as qualitative research, 88 news content obtained from the Google News platform were examined with thematic analysis method and answers to the research questions were sought. The results show that the main reasons for anti-tourism protests are tourist behaviour, destruction of natural resources, accommodation problems, deficiencies of local governments and exceeding the carrying capacity. In addition, it was determined that the protests against tourists are related to the lack of economic and social benefits that local people obtain from tourism. The study emphasized that anti-tourism movements can damage the international image of the region by creating negative feelings such as fear and anxiety in tourists. Recommendations for local governments include tourist entry and accommodation regulations, environmental measures and guiding tourists' behaviour. The study states that sustainable tourism can be achieved through cooperation between local people, tourists and governments, and recommends that more comprehensive research be conducted in the future. The theoretical importance of this study is that it draws attention to the fact that the basis of anti-tourism protests is not the tourist-local community relationship, but the lack of social and economic welfare and the unsustainable use of resources.